The Impacts of the Implementation of Clean Energy in Industry: A Literature Review - Jardim, Edson de Jesus; de Lucca Filho, João (Revista Interface Tecnológica, 2025)
Solar energy is considered one of the most promising renewable sources for reducing dependence on fossil fuels, reducing greenhouse gas emissions, promoting sustainable practices and strengthening business competitiveness. The objective of this study is to identify the sectors and potential benefits of adopting photovoltaic panel technology, examine the incentives available for its implementation and provide information on clean energy and sustainability. The methodological approach employed involved bibliographic and documentary reviews, with the intention of identifying the most relevant studies that deal with low-carbon energy and the transformation of the energy matrix. The results indicate that, among the main advantages of adopting solar energy, the enhancement of the industrial brand, tax benefits and cost reduction stand out. Therefore, its implementation in industries is seen as viable, taking into account the environmental, economic and social benefits in addition to the cost-benefit ratio. This study also presents a comprehensive overview of the negative impacts that can be avoided with the adoption of photovoltaic solar energy, in addition to suggesting directions for future research on the subject. It is concluded that the integration of renewable energy into industry is an essential strategy to move towards a sustainable development model.